Integrating Game-Based-Learning to Improve Students’ Essay Writing in High School Sociology - Ahmad Nashihin Salim; Rosmawijah Jawawi; Masitah Shahrill; Jainatul Halida Jaidin; Juraidah Musa (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
This study integrates game-based learning (GBL) in sociology lessons to investigate its impact on students’ essay writing. The study had a sample size of seven students from a Year 12 Sociology class in one of the high schools in Brunei Darussalam. This qualitative research made use of data collection instruments consisting of pre-test and post-test essay questions, semi-structured interviews, and lesson observations. Findings from the study have shown that the implementation of games that utilize civilization-building elements such as city building and resource management in a sociology lesson had a significant impact on students' performance in essay writing, specifically the quality of their argument, provided that they were used within the right context. The study also found an increase in students’ motivation, collaboration, and enjoyment of learning, attributing this to the games' designs and their easy accessibility via smartphones. Students’ perceptions of the use of GBL indicated a willingness to use it again as a learning tool in the near future. The findings provided insights into this area of study and may be able to provide useful information to educators, especially sociology teachers, who wish to make use of games to aid in making their students' learning an enjoyable experience in their lessons.